Preparation and performance of 1–3 multi-element piezoelectric composites. Issue 5 (June 2015) - Huang, S.F.; Lin, X.J.; Xu, D.Y.; Zhou, M.J.; Li, M.M.; Xie, S.H.; Cheng, X.
Abstract: A 1–3 type multi-element piezoelectric composite was fabricated using silicon as decoupling material to ensure the independence of transmitted acoustic beam and strengthen the signal power. The consistency and acoustic coupling of all elements in the composite were investigated. The results showed that the piezoelectric, dielectric and ferroelectric properties, and the electromechanical coupling properties of each element in the composite exhibited excellent consistency. The good decoupling effect of the silicon filled in the composite increased the response signal decay rates larger than 98%, which effectively decreased the acoustic coupling between adjacent elements. Therefore, the composite showed a potential use in multi-beam transmitter arrays.